2012
DOI: 10.3109/10799893.2012.660533
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the responses of saccharin in context with melatonin receptors on the melanophores of the fishLabeo rohita(Ham.)

Abstract: The hormone melatonin regulates the biological clock and assist in various other physiologies of vertebrates. Present work is intended to check the affinity of saccharin towards the melatonin receptors and the possible role of saccharin interference in the melatonin physiology. The present in vitro study is based on the working model of isolated scale melanophores in the dorso-lateral region of Labeo rohita. The pigment cells were incubated in the agonist and the antagonists within a limited time frame and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Likening dopaminergic neurons to the melanocytes, they are not just neurons but specialized sensors of positions and environment [30]. The melanin pigments are most likely regulators of signal transduction in the entire movement coordination system of the brain, such that when nerve impulse passes, the Tubulin-motor protein complex are assembled from the MTOC or move pigments along their length in these neurons, thus generating specific information as to the nature of the movement and the extent of muscle contraction required for such movement [31]. This is also evident in the fishes as the scales have been found not to only contribute to the biological adaptation of fishes in water (counter shading) but senses the environment and contribute to movement and balance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Likening dopaminergic neurons to the melanocytes, they are not just neurons but specialized sensors of positions and environment [30]. The melanin pigments are most likely regulators of signal transduction in the entire movement coordination system of the brain, such that when nerve impulse passes, the Tubulin-motor protein complex are assembled from the MTOC or move pigments along their length in these neurons, thus generating specific information as to the nature of the movement and the extent of muscle contraction required for such movement [31]. This is also evident in the fishes as the scales have been found not to only contribute to the biological adaptation of fishes in water (counter shading) but senses the environment and contribute to movement and balance [32].…”
Section: Discussionmentioning
confidence: 99%
“…And some of these non‐dermal types of chromatophores are also responsive to melatonin 8–10 . Melatonin is generally considered to be responsible for the centripetal lodging of pigments in melanophores of fishes and amphibians resulting in their body blanching 11 . Recently Kulczykowska et al 12 have reported that the stress hormone cortisol stimulates melatonin secretion from flounder skin explants in a dose‐dependent fashion.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Melatonin is generally considered to be responsible for the centripetal lodging of pigments in melanophores of fishes and amphibians resulting in their body blanching. 11 Recently Kulczykowska et al 12 have reported that the stress hormone cortisol stimulates melatonin secretion from flounder skin explants in a dose-dependent fashion. This indicates that melatonin and its metabolites can mediate the cutaneous antioxidative defense in fish, as for mammals like extrapineal melatonin synthesis 13 ; even beneficial to protect mitochondria in human retinal pigment epithelium under oxidative stress.…”
Section: Introductionmentioning
confidence: 99%